Determination of energy constants of materials and their critical masses during crushing of solids - Purtseladze Irina; Makhmaisaev Aziz (E3S Web of Conferences, 2023)
To consider the issue of optimization of technical indicators in determining the values of the energy constants of materials and their critical masses in the process of crushing solids. Energy analysis of construction processes was carried out when crushing mineral materials with crushers of various designs, ball mills and other mills to obtain bulk materials (crushed stone of various sizes, clinets, sand, etc.). The energy constants of materials and their critical masses have been determined, which are crucial for assessing the properties of materials and establishing their resistance to destruction in various processes of interaction with external influences. The results of stone crushing processes by crushers and concrete samples by a press are presented. The value of the energy constant of concrete that characterizes it most fully, taking into account all its physical properties that affect the resistance to external influences, has been clarified. The developed methods can be recommended for practical use.